A new perspective on mechanisms governing skeletal complications in type 1 diabetes - Seref-Ferlengez, Zeynep (Ann N Y Acad Sci, 2016)
This review focuses on bone mechanobiology in type 1 diabetes (T1D), an area of research on diabetes-associated skeletal complications that is still in its infancy. We first provide a brief overview of the deleterious effects of diabetes on the skeleton and of the knowledge gained from studies with rodent models of T1D. Second, we discuss two specific hallmarks of T1D, low insulin and high glucose, and address the extent to which they affect skeletal heath. Third, we highlight the mechanosensitive nature of bone tissue and the importance of mechanical loading for bone health. We also summarize recent advances in bone mechanobiology that implicate osteocytes as the mechanosensors and major regulatory cells in the bone. Finally, we discuss recent evidence indicating that the diabetic bone is “deaf” to mechanical loading and that osteocytes are central players in mechanisms that lead to bone loss in T1D.